The Wnt-specific astacin proteinase HAS-7 restricts head organizer formation in Hydra - Ziegler, Bérénice; Yiallouros, Irene; Trageser, Benjamin; Kumar, Sumit; Mercker, Moritz; Kling, Svenja; Fath, Maike; Warnken, Uwe; Schnölzer, Martina; Holstein, Thomas W.; Hartl, Markus; Marciniak-Czochra, Anna; et al. (BMC biology, 2021)
The Hydra head organizer acts as a signaling center that initiates and maintains the primary body axis in steady state polyps and during budding or regeneration. Wnt/beta-Catenin signaling functions as a primary cue controlling this process, but how Wnt ligand activity is locally restricted at the protein level is poorly understood. Here we report a proteomic analysis of Hydra head tissue leading to the identification of an astacin family proteinase as a Wnt processing factor.
Gesehen am 25.06.2021